Giant convecting mud balls of the early solar system - Bland, Phil; Travis, B. (American Association for the Advancement of Science (A A A S), 2017)
Carbonaceous asteroids may have been the precursors to the terrestrial planets, yet despite their importance, numerous attempts to model their early solar system geological history have not converged on a solution. The assumption has been that hydrothermal alteration was occurring in rocky asteroids with material properties similar to meteorites. However, these bodies would have accreted as a high-porosity aggregate of igneous clasts (chondrules) and fine-grained primordial dust, with ice filling much of the pore space. Short-lived radionuclides melted the ice, and aqueous alteration of anhydrous minerals followed. However, at the moment when the ice melted, no geological process had acted to lithify this material. It would have been a mud, rather than a rock. We tested the effect of removing the assumption of lithification. We find that if the body accretes unsorted chondrules, then large-scale mud convection is capable of producing a size-sorted chondrule population (if the body accretes an aerodynamically sorted chondrule population, then no further sorting occurs). Mud convection both moderates internal temperature and reduces variation in temperature throughout the object. As the system is thoroughly mixed, soluble elements are not fractionated, preserving primitive chemistry. Isotopic and redox heterogeneity in secondary phases over short length scales is expected, as individual particles experience a range of temperature and water-rock histories until they are brought together in their final configuration at the end of convection. These results are consistent with observations from aqueously altered meteorites (CI and CM chondrites) and spectra of primitive asteroids. The “mudball” model appears to be a general solution: Bodies spanning a ×1000 mass range show similar behavior.